(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The emergence of bioethics responds to the emergence of new moral problems related to the change in the place of science in terms of the application of its results and its impact on the lives of people, society and nature. The proceduralism in bioethics was supported by the creation of structures aimed at training, investigating and in other cases, at becoming constitutive and deliberative spaces for the reduction of ethical conflicts. They are constituted in structures from which the various methodological proposals in bioethics reach their legitimacy, since they provide the field from which to make their implementation effective in specific situations. It is worth highlighting the role played by the centers created in academic institutions, chairs and bioethics committees. Institutional development in the framework of the universities was key to the extension and consolidation of bioethics. The present work aims to analyze the instrumentalization of the epistemic resources of bioethics in Higher Education in Cuba.